"It's ok, mom. I got it!": Exploring the experiences of young adults with intellectual disabilities in a postsecondary program affected by the COVID-19 pandemic from their perspective and their families' perspective. (September 2021) - Spencer, Patricia; Van Haneghan, James P; Baxter, Abigail; Chanto-Wetter, Alexandra; Perry, Lauren
Students' resilience in a postsecondary program for individuals with an intellectual disability impacted by the COVID-19 disruption and the challenges they faced during this time was captured in the context of social network analysis interviews that included students' and families' experiences as they managed the pandemic. Students' experiences spoke to their resilience in using the skills they gained through the program to navigate the COVID-19 disruption even though it was sometimes tricky. Parents' experiences revealed their increased confidence and sense of pride in their adult children when they observed growth in independence, self-determination, and familiarity with technology. Innovative and engaging instructional practices and e-mentoring support offered by peer mentors motivated students in their academics and encouraged their social development during this time. Student and parent experiences offer hope that young adults with an intellectual disability can gain skills in a postsecondary program that better prepares them to meet life's challenges.